2016
DOI: 10.1111/jch.12849
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Left Ventricular Wall Thickness, Myocardial Shortening, and Ejection Fraction in Hypertensive Heart Disease: Insights From Cardiac Magnetic Resonance Imaging

Abstract: Hypertensive heart disease is often associated with a preserved left ventricular ejection fraction despite impaired myocardial shortening. The authors investigated this paradox in 55 hypertensive patients (52±13 years, 58% male) and 32 age‐ and sex‐matched normotensive control patients (49±11 years, 56% male) who underwent cardiac magnetic resonance imaging at 1.5T. Long‐axis shortening (R=0.62), midwall fractional shortening (R=0.68), and radial strain (R=0.48) all decreased (P<.001) as end‐diastolic wall thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 44 publications
2
22
1
Order By: Relevance
“…Deformation parameters change in different directions during the progression of myocardial disease, however, its instantaneous change in this investigation could not be attributed to this. The paradoxical phenomenon in our study that decreased longitudinal and circumferential shortening with preserved ejection fraction is commonly seen in patients with hypertension [25][26][27]. As the afterload increased, longitudinal and circumferential shortening decreased while the wall thickened as a compensation allowing a preserved ejection fraction.…”
Section: Discussioncontrasting
confidence: 45%
“…Deformation parameters change in different directions during the progression of myocardial disease, however, its instantaneous change in this investigation could not be attributed to this. The paradoxical phenomenon in our study that decreased longitudinal and circumferential shortening with preserved ejection fraction is commonly seen in patients with hypertension [25][26][27]. As the afterload increased, longitudinal and circumferential shortening decreased while the wall thickened as a compensation allowing a preserved ejection fraction.…”
Section: Discussioncontrasting
confidence: 45%
“…The relationships between LV geometry and ejection fraction (EF) have been extensively investigated in pathological hypertrophy 10,11 whilst the association in a physiological model, such as the AH, remains incompletely understood. Since the interrelationship between ventricular wall thickness, cavity dimension and EF is complicated, a better comprehension of the relationship between the thickness of the LV wall, EF and myocardial ɛ has been aided using mathematical modelling 10,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modelling helps as it eliminates confounding factors and quantifies the individual effects of geometric and physiological changes. The understanding provided by modelling studies has now been applied to hypertensive hypertrophic ventricular disease 11 . It has been shown that using mathematical modelling 10 and confirmed observational clinical data, that increasing LV wall thickness and/or myocardial ɛ independently leads to increased EF 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The European guidelines do not place much emphasis on myocardial dysfunction as a marker of TOD; however, in this study, 14% of patients had reduced ejection fraction and 42% had impaired long‐axis function. Ejection fraction was generally preserved in our cohort, but using this parameter alone may miss significant cardiac systolic dysfunction in the presence of LVH …”
Section: Discussionmentioning
confidence: 79%